2007
DOI: 10.1182/blood-2006-12-061283
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive phosphoinositide 3-kinase/Akt activation represents a favorable prognostic factor in de novo acute myelogenous leukemia patients

Abstract: The phosphoinositide 3-kinase (PI3K/Akt) pathway is activated in acute myelogenous leukemia (AML) and is promising for targeted inhibition. Ninety-two patients with primary AML were analyzed for PI3K/Akt constitutive activation. Fifty percent of the patients presented with constitutive PI3K activation (PI3K ؉ ). No difference was observed between PI3K ؉ and PI3K ؊ groups concerning age, sex, white blood cell count, lactate dehydrogenase (LDH) level, bone marrow blast cells, French-American-British (FAB) classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
130
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 14 publications
4
130
0
5
Order By: Relevance
“…2 The genes encoding the PI3K catalytic and regulatory chains are members of multi-gene families. Historically, the p110a isoform has been the best-characterized catalytic subunit; however, it has been recently shown that the p110d isoform may play a larger role in leukemogenesis [3][4][5] and tumor surveillance than expected previously. The activation of the PI3Kd isoform does not appear to be due to genetic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…2 The genes encoding the PI3K catalytic and regulatory chains are members of multi-gene families. Historically, the p110a isoform has been the best-characterized catalytic subunit; however, it has been recently shown that the p110d isoform may play a larger role in leukemogenesis [3][4][5] and tumor surveillance than expected previously. The activation of the PI3Kd isoform does not appear to be due to genetic mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Cells harboring these mutations may be refractory to Akt inhibitors which target the kinase domain but may be more sensitive to inhibitors which target the PH domain (Carpten et al, 2007). The role of overexpression of the different Akt isoforms in cancer prognosis is controversial (Kornblau et al, 2006, Tamburini et al, 2007. Some studies have suggested that elevated Akt expression is associated with a poor prognosis in breast (Kirkegaard et al, 2005) and hematopoietic (Kornblau et al, 2006) cancers.…”
Section: Therapeutic Targeting Of the Pi3k/akt/pten/mtor And Raf/mek/mentioning
confidence: 99%
“…Some studies have suggested that elevated Akt expression is associated with a poor prognosis in breast (Kirkegaard et al, 2005) and hematopoietic (Kornblau et al, 2006) cancers. Controversially it has been observed recently that constitutive PI3K/Akt activation is a favorable prognostic factor in AML patients (Tamburini et al, 2007) as Akt activation may keep a high percentage of the cells in S phase which renders them sensitive to chemotherapeutic drugs. These and other studies document the complexity of enhanced Akt expression which may make certain cells more sensitive or resistant to certain anti-cancer therapies.…”
Section: Therapeutic Targeting Of the Pi3k/akt/pten/mtor And Raf/mek/mentioning
confidence: 99%
“…[3][4][5] Studies have shown that the PI3K/Akt/mTOR pathway is constitutively activated in 50-70% of acute myeloid leukemia (AML) cases, suggesting that this pathway could constitute a therapeutic target. [6][7][8][9][10][11] p53 is the most frequently inactivated protein in human cancer, and more than 50% of all solid tumors carry p53 mutations in the TP53 gene that abrogate its DNA binding and transactivation activity. 12 Although TP53 mutations rarely occur in AML, it has been suggested that inactivation of wild-type p53 frequently occurs through binding to its principal cellular regulator murine double minute 2 homologue (Mdm2).…”
Section: Introductionmentioning
confidence: 99%